2020
DOI: 10.3390/agronomy10030370
|View full text |Cite
|
Sign up to set email alerts
|

Application of Directly Brewed Compost Extract Improves Yield and Quality in Baby Leaf Lettuce Grown Hydroponically

Abstract: The aim of this work was to study whether the application of a directly brewed compost extract (added in the nutrient solution or by microsprinkler) could be used to improve the yield and quality of baby leaf red lettuce growing in a floating system, and to control the incidence of Pythium irregulare. Its effect on the quality of fresh-cut red lettuce was also studied. For this, two experiments were carried out over two growing cycles (winter–spring and autumn). The results showed that the use of compost extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…The addition of CE to the fertilizers tested did not affect adversely the yield, except for control plants where a decrease was observed. The latter result is in agreement with that obtained by Gimenez et al [20], who applied a CE by micro-sprinkler in baby leaf lettuce grown hydroponically and obtained a lower yield than the control. Other authors [27] have reported that the application of two microbial compost teas did not result in improved crop yields in spinach.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The addition of CE to the fertilizers tested did not affect adversely the yield, except for control plants where a decrease was observed. The latter result is in agreement with that obtained by Gimenez et al [20], who applied a CE by micro-sprinkler in baby leaf lettuce grown hydroponically and obtained a lower yield than the control. Other authors [27] have reported that the application of two microbial compost teas did not result in improved crop yields in spinach.…”
Section: Discussionsupporting
confidence: 93%
“…In general, nitrate contents slightly decreased after 6 days of storage for all the treatments (except DMPP treatments) according to the results obtained by Gomez et al [34] in celery, Miceli et al [35] in rocket leaves, and Giménez et al [20] in lettuce. This is because postharvest nitrate reduction requires exogenous microbial nitrate reductase activity, which is unlikely to be achieved without visible loss of quality [36].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Results of soil samples analysis was shown in table (1). Results of soil analysis showed very low nitrogen content of the studied samples, clay loam texture, neutral alkalinity and salinity within acceptable range.…”
Section: A Soil Sample Analysismentioning
confidence: 89%
“…The phenolic contents of seeds are linked to environmental conditions (Salazar-López et al, 2018). The application of some compost increased the production of phenolics and flavonoids contents (Lakhdar et al, 2011;Giménez et al, 2020). The availability of nitrogen should influence the amounts of phenolics more strongly than terpenoids because phenolics are produced in the same shikimic acid pathway as aromatic amino acids as suggested previously.…”
Section: Total Phenolics and Total Flavonoids Contents Of Sorghum Seedsmentioning
confidence: 89%